A Women Infertility: An Overview - Upadhyay, Yash; Chhabra, Anshu; Nagar, Jagdish Chandra (Asian Journal of Pharmaceutical Research and Development, 2020)
Female infertility is the major disorder which has altered the man kind foe lack of conception and reproducibility, stressful world, excess radiation, lack of biological food, genetically disorder ,changing life style, increased electronic discharge have resulted the female infertility. Infertility/ childlessness cause great personal suffering & distress. Most of this agony & misery is hidden from the public gaze. That is the reason this topic is not discussed about openly. The dismal ignorance & neglect about the causes of childlessness and its treatment are main reason for the lack of public support for childless couple. Female fertility can be limited or diminished or destroyed in a number of ways. Women have a finite number of germs cells and follicles that are available for a limited period, from menarche to menopause, during their lifetimes.